2020
DOI: 10.1371/journal.pone.0236250
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with multidrug-resistant tuberculosis (MDR-TB) in Bhutan: A nationwide case-control study

Abstract: Background Multidrug-resistant tuberculosis (MDR-TB) is a growing public health concern globally. In Bhutan, the rates of MDR-TB are high. Data on the risk factors of MDR-TB that can help inform policies are limited in Bhutan. This study aimed to determine the risk factors associated with MDR-TB. Methods A nationwide unmatched case-control study was conducted that included 79 MDR-TB cases and 118 controls. Data was collected by trained health workers through interviews using a structured questionnaire. Logisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
1
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 20 publications
0
10
1
3
Order By: Relevance
“…6 However, a study conducted in Bhutan showed that having more than 2 rooms in the house also emerged to be marginally associated with having MDR-TB. 17 This could be due to differences in the classification of variables and differences in the housing conditions. The occurrence of MDR-TB was strongly associated with the previous treatment with anti-TB drugs.…”
Section: Discussionmentioning
confidence: 99%
“…6 However, a study conducted in Bhutan showed that having more than 2 rooms in the house also emerged to be marginally associated with having MDR-TB. 17 This could be due to differences in the classification of variables and differences in the housing conditions. The occurrence of MDR-TB was strongly associated with the previous treatment with anti-TB drugs.…”
Section: Discussionmentioning
confidence: 99%
“…It can be seen that the failure of a history of treatment has a risk of 2.9 times the incidence of MDR TB (aOR= 2.95; 95% CI= 27.3 to 30.1). In addition, it is also relevant to the study conducted by Tenzin (Tenzin et al, 2020) that past history of TB treatment had a 5.9 times risk of MDR TB incidence (aOR= 5.90; 95% CI= 2.55 to 13.64).…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted in Bhutan, it was shown that previous TB treatment, inadequate sleep duration, and traveling by public transport were risk factors associated with MDR-TB in Bhutan. Strengthening early case detection, strengthening treatment strategies, improving treatment adherence, and raising awareness can help control the growing MDR-TB epidemic (Tenzin et al, 2020). Several of these studies have been carried out in various parts of the world including South Asian countries to determine risk factors for MDR-TB.…”
mentioning
confidence: 99%
“…Among the most prevalent are poverty, overcrowding, HIV co-infection, diabetes, alcoholism, smoking, cavitary disease and even young age. Thus, in clinical practice, it is essential to assess general risk factors as well as ones speci c to the region of residence of the patients [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%